Pemanfaatan Limbah Logam Aluminium Sebagai PAC Untuk Proses Penjernihan Air Sumur - Azzahra, Nyak; Zaini, Halim; Rahmawati, Cut Aja (Politeknik Negeri Lhokseumawe, 2023)
Utilization of aluminum metal powder waste left over from the plate rack which is wasted can apparently provide economic value as raw material for making coagulants. Aluminum powder waste contains 88.74% aluminum. The high aluminum content makes plate rack waste potentially as raw material for the manufacture of polyaluminium chloride (PAC). This study begins with the manufacture of AlCl3 monomers on 4 grams of aluminum metal weight, by varying NaOH concentrations (44, 45, 46, 47 and 48%) and variations in HCl concentrations (31, 32 and 33%). Next the AlCl3 monomer is converted to PAC polymer. The results on variation of 48% NaOH and 32% HCl with pH 3.6 and specific gravity 1.23 g / ml. This result is in accordance with SNI 06-3822-1995 quality standards. This study also tested the ability of PAC to reduce turbidity in well water, with a pH of 4.30 and a decrease in turbidity of 94.94%. Can produce PAC that is more economical and has met the standard qualityof conventional SNI PAC.